Does Sustainability Risk and Corporate Governance Quality Matter to Investors’ Level of Investment? - Suryawati , Rindah Febriana; ., Amaliyah; Widyatama, Arif; Abdullah , Mazni (Journal of Ecohumanism, 2025)
This study examines the impact of sustainability risk (SR) and corporate governance quality (CGQ) on investors’ investment (CG) decisions. Using the 2x2 experimental design method, our findings indicate that firms with low sustainability risk are more appealing to investors than those with high sustainability risk. Besides the risk factor, a firm’s high corporate governance quality offers more investment assurances for investors compared to a firm with poor governance quality. Overall, this study demonstrates the impact of the SR and CGQ on the investment judgement level. This study also lends credence to the stakeholder theory by demonstrating how firms may achieve long-term stability and profitability by managing their sustainability risks. Hence, sustainability risk assessment is an essential consideration in investment decisions, in addition to conventional financial factors. Research on the influence of SR and CGQ on investment decisions is limited. Moreover, the majority of prior research measured corporate governance based on corporate governance structure. Therefore, our study contributes to the extant literature by documenting the findings using an experimental website approach, whereby CGQ and SR were distinctly manipulated in the experimental materials to assess their influence on investment judgement levels.